Evaluation of the parental satisfaction of developmentally delayed pediatric patients undergoing dental surgery with the ’’pediatric anesthesia parent satisfaction (PAPS)’’ survey - Sargın, Mehmet; Toprak, Hatice; Çelik, Jale Bengi (The European Research Journal, 2020)
Objectives: The aim of the present study was to assess parental satisfaction of developmentally delayed pediatric patients undergoing dental surgery and compare this to satisfaction with anesthesia care for children without developmentally delayed. Methods: Therefore, two different groups were approached and compared to matching controls. ’’Pediatric anesthesia parent satisfaction (PAPS)’’ survey was used to evaluate parental satisfaction in the present study. The PAPS survey was administered to 50 parents of developmentally delayed pediatric patients (Group I) and 30 parents of children without developmentally delayed (Group II). However, due to the shortcomings in the questionnaires, 5 participants from Group I and 4 from Group II were excluded from the study. Results: In the ’’Before anesthesia’’, ’’After anesthesia’’, ’’Hospital team’’ and ’’Anesthesia team’’ parts of survey no statistically significant difference was found between the groups. In the ‘‘Before anesthesia’’ part the lowest score was given in response to Q5 item (The anesthesia team explained to me how my child might feel physically and emotionally after anesthesia and surgery). The mean score of Q5 item was 2.73 ± 1.77 in Group I and 2.36 ± 1.40 in Group II. Conclusions: In conclusion, it was found that there is no difference between parental satisfaction of children with developmentally delayed and parental satisfaction of developmentally delayed pediatric patients.